ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI KINERJA PEGAWAI PADA SMA NEGERI 11 KOTA JAMBI - Sriwiyanti, Sriwiyanti; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2019)
The civil servants’ at SMAN 11 Jambi city is still using conventional Microsoft excel application asemploye’sperformrnce data admistrative processor in makig SKP. This process needs long time, reguireslarge enough memory storage for each employee. The researcher designed an administrative informationsystem for the employees’performancewhosethe output was in the form of SKP reports. This system is astrategy to facilitate staff’s administration activities so as improving employees’ quality and potency. Thepurpose of this research is analyzing and designing administrative information systems for employee’sperformance in SMA Negeri 11 Kota Jambi. The design of this information system is useful for vice ofprincipal and the staff for PKB, to help and add insight relates to PKB in processing administrative dataon employee’s performances, as well as to facilitate coordination between Supervisors, Principaland thevice of principal, teachers and administrative staff. The design of this system uses UML tools, namelyUsecase diagrams, activity diagrams and class diagrams. This study produced an administrativeinformation system prototype for employee’s performance that can manage target activities andrealization of civil servants in a computerized manner. Analysis and design of this information system canminimize the problems that occur,